1995
DOI: 10.1073/pnas.92.8.3376
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells express a peripheral cannabinoid receptor with differential sensitivity to anandamide and palmitoylethanolamide.

Abstract: Mast cells are multifunctional bone marrowderived cells found in mucosal and connective tissues and in the nervous system, where they play-important roles in tissue inflammation and in neuroimmune interactions. Very

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
424
7
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 589 publications
(461 citation statements)
references
References 40 publications
18
424
7
6
Order By: Relevance
“…Further support to this proposal comes from the fact that palmitylethanolamide may exert both analgesic Ž . Calignano et al, 1998;Jaggar et al, 1998; present study Ž and anti-inflammatory effects Benvenuti et al, 1968;Facci . et al, 1995;Mazzari et al, 1996 .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Further support to this proposal comes from the fact that palmitylethanolamide may exert both analgesic Ž . Calignano et al, 1998;Jaggar et al, 1998; present study Ž and anti-inflammatory effects Benvenuti et al, 1968;Facci . et al, 1995;Mazzari et al, 1996 .…”
Section: Discussionsupporting
confidence: 49%
“…Palmitylethanolamide, which was isolated from tissues more than Ž . three decades ago Bachur et al, 1965 , was shown to have Ž marked anti-inflammatory Benvenuti et al, 1968;Facci et . al., 1995;Mazzari et al, 1996 and antinociceptive effects Ž when administered as a drug Calignano et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism appears to be mediated by a speci®c Na + -independent carrier protein in as much as it is saturable, temperature-dependent, selective, and apparently inhibited by various AEA analogues such as AM404 (for review, see Hillard & Jarrahian, 2000). The presence of a de®ned transport mechanism for PEA would provide an interesting pharmacological target for the treatment of in¯ammatory diseases, since a blockade of PEA transport would result in elevated extracellular concentrations of PEA, and hence, augmentation of the anti-in¯ammatory and anti-nociceptive e ects of this compound (Facci et al, 1995;Mazzari et al, 1996;Jaggar et al, 1998;Calignano et al, 1998). This would be analogous to the situation for AEA, where both the duration and intensity of the hypotensive e ects of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to PEA, Facci et al (1995) proposed that it acts as an endogenous physiological ligand for the CB 2 receptor. However, more recent data have indicated that PEA does not bind with high a nity to either of the two cannabinoid receptor subtypes (Showalter et al, 1996;antagonizing in¯ammatory processes (Facci et al, 1995;Mazzari et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation